Ghrelin inhibits oxLDL-induced inflammation in RAW264.7 mouse macrophages through down-regulation of LOX-1 expression via NF-ÎºB signaling pathway - Sun, N; Wang, H; Wang, L (Cellular and Molecular Biology, 2016)
Oxidized low-density lipoprotein (oxLDL) is one of the many causes of the initiation and progression of atherosclerosis, which can subsequently promote the uptake of oxLDL by macrophages and lead to inflammation in the blood vessels. In the present study, we evaluated the protective effects of ghrelin on oxLDL-induced RAW264.7 mouse macrophages. Ghrelin was able to inhibit the release of several pro-inflammatory cytokines including tumor necrosis factor (TNF)-Î± and interleukin (IL)-6. In addition, ghrelin also inhibited the expression of Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) in oxLDL treated macrophages. Furthermore, we demonstrated that ghrelin could inhibit the expression of p-IÎºBÎ±, and the inhibitory effects could be blocked by BAY 117082. Taken together, ghrelin possesses anti-inflammatory effects on oxLDL-induced inflammation in macrophages, suggesting that it can prevent or treat atherosclerosis, and deserves to be further studied and developed to be potent drug for treating atherosclerosis.